2012
DOI: 10.3389/fnhum.2011.00182
|View full text |Cite
|
Sign up to set email alerts
|

The Heterogeneous Nature of Number–Space Interactions

Abstract: It is generally accepted that the mental representation of numerical magnitude consists of a spatial “mental number line” (MNL) with smaller quantities on the left and larger quantities on the right. However, the amount of dissociations between tasks that were believed to tap onto this representational medium is accumulating, questioning the universality of this model. The aim of the present study was to unravel the functional relationship between the different tasks and effects that are typically used as evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
48
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 56 publications
3
48
0
Order By: Relevance
“…In contrast, in a parity judgment task, the SNARC effect disappeared with a verbal load but was unaffected by a visuospatial load. Together, these observations indicate that the formation of number-space associations requires availability of working memory resources: The SNARC effect in a parity judgment context needs verbal working memory resources, whereas the SNARC effect in a magnitude comparison needs visuospatial working memory resources (see also van Dijck, Gevers, Lafosse, & Fias, 2012). In line with this, a principal component analysis on parity and magnitude comparison performance tested within the same subjects showed that the SNARC effect in a parity judgment task and in a magnitude comparison task loaded on two independent components (van Dijck et al, 2012).…”
mentioning
confidence: 86%
“…In contrast, in a parity judgment task, the SNARC effect disappeared with a verbal load but was unaffected by a visuospatial load. Together, these observations indicate that the formation of number-space associations requires availability of working memory resources: The SNARC effect in a parity judgment context needs verbal working memory resources, whereas the SNARC effect in a magnitude comparison needs visuospatial working memory resources (see also van Dijck, Gevers, Lafosse, & Fias, 2012). In line with this, a principal component analysis on parity and magnitude comparison performance tested within the same subjects showed that the SNARC effect in a parity judgment task and in a magnitude comparison task loaded on two independent components (van Dijck et al, 2012).…”
mentioning
confidence: 86%
“…Furthermore, number-space associations in the parity judgment and magnitude classification tasks could be selectively abolished by a verbal and visuospatial WM load respectively (van Dijck et al, 2009). Moreover, findings from a principle component analysis showed that SNAs in the parity judgment and magnitude classification tasks were placed in two separate components (van Dijck, Gevers, Lafosse, & Fias, 2012), thus suggesting that spatial-numerical interactions in implicit and explicit magnitude processing tasks potentially arise from qualitatively different cognitive mechanisms. Furthermore, while hemi-neglect patients featured regular spatial-numerical interactions in the parity judgment task, where access to numerical magnitude is implicit, they show atypical number-space associations in the explicit magnitude classification task (Priftis, Zorzi, Meneghello, Marenzi, & Umilta, 2006;Zorzi et al, 2012).…”
mentioning
confidence: 95%
“…Importantly, several studies have shown the difficulties of LN patients in explicitly accessing larger magnitudes on the MNL (Masson, Pesenti, & Dormal, 2013;Priftis et al, 2006;Van Dijck, Gevers, Lafosse, & Fias, 2012;Vuilleumier, Ortigue, & Brugger, 2004;Zorzi et al, 2002Zorzi et al, , 2012 see Umiltà, Priftis, & Zorzi, 2009, for a review). LN patients' impairment in processing numerical magnitude might be explained by their difficulty in orienting spatial attention towards the left in the imaginal space, and thus in exploring the left part of the number space (Zorzi et al, 2002; but see Aiello et al, 2012, for a contrasting view).…”
mentioning
confidence: 99%